Gestión administrativa del área de producción y ventas de la Comercializadora Santa Rosa - Jerez Gómez, Kevin Abel (2021)
The company Comercializadora Santa Rosa began activities in 2015, it is located in La Unión Parish, Babahoyo Canton, Los Ríos Province. It has had great growth to date, but currently presents management problems in the production area, specifically in the chicken slaughter process, generating product losses that compromise 10% of the economic income from sales, to solve this deficiency You must implement solutions that reduce or eliminate the loss of product, having as a possible solution the change of your slaughter system. Additionally, the management of the sales area must develop strategies to retain its customers, since it must make changes in its sales model related to customer satisfaction and tastes, this threatens the loss of customers, which translates into losses economic. However, it is proposed to seek solutions that resolve this conflict.